ESTIMATION OF CREDIT RISK LOSSES AND MODELING OF BANK LIQUIDITY RISK - OLIINYK, ANDRIY (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The recent crisis in the banking system has shown that the functions of banking risk management have not been given sufficient attention. This jeopardized the efficiency of the entire domestic banking system. Insufficient efficiency of the risk assessment and modeling system in domestic banks has led to a number of negative consequences for the Ukrainian economy as a whole. Therefore, the problem of developing scientific and methodological approaches to the assessment and modeling of banking risks is relevant and of practical importance. The purpose of the article is to assess credit risk losses, model liquidity risk of banks and develop practical recommendations for the introduction of modeling of liquidity risk in the activities of domestic banks. Approaches to defining the concept of banking risk are analyzed. It is established that banks operate in conditions of high credit risks which result in significant amounts of non-performing loans. Credit risk losses were assessed according to the scenarios of compromise and aggressive risk lending position. The Van Den-End liquidity stress testing model was used as a tool to identify negative market effects and financial liquidity shocks. The general tendency of the ratio of liquidity buffer to liquidity deficit taking into account the risk is determined and substantiated and the forecast for the future period is made. We found that the efficiency of the bank’s loan portfolio is low. However, there is a dynamic increase in the efficiency of the bank’s loan portfolio from 0.00982 at the beginning to 0.09447 at the end of the year. This trend is positive. According to the results of the simulation, we found that with a sufficient amount of liquidity buffers of assets in JSC "PrivatBank" their quality remains low, because the share of secondary reserves in the bank is critically low. The bank is state-owned and is constantly refinanced on the interbank credit market. This allows the bank to work only on the first stage of the scenario of this model. The bank is practically protected from risk shocks by government securities.